Microbiological and physical-chemical quality of water for human consumption and the relationships with health: study in an agricultural community in state São Paulo - Ribeiro de Araújo, Glauco Fernando; de Abreu Tonani, Karina Aparecida; Julião, Fabiana Cristina; de Oliveira Cardoso, Osmar; Igor da Silva Alves, Renato; Frari Ragazzi, Mariana; de Freitas Sampaio, Carolina; Segura-Muñoz, Susana Inés (O Mundo da Saúde, 2011)
In this study we evaluated the relationship between health and environmental sanitation in the context of the process of social development, analyzing the quality of the water for human consumption in Sepé Tiarajú-SP Agricultural Community, which constitutes a project of sustainable development. During the inquiry we identified the presence of pathogenic parasites and coliform bacteria in collected water samples in the points of collective supplying, in the containers of water storage of housings, in the springs and the Serra Azul River range. Parasitological and bacteriological analyzes of collected samples had been carried through in procedures established by Standard Methods for the Examination of Water and Wastewater (APHA) and CETESB – Companhia de Tecnologia de Saneamento Ambiental (Company of Technology for Environmental Sanitation). Results lead us to consider the water used in some communities as a risk factor for the health of human beings that use that it. We believe the development of a work of sanitary education for rural populations, the adoption of preventive measures aiming at the preservation of water sources and the treatment of waters already compromised, allied to techniques of waste treatment, are tools necessary for greatly diminishing the risk of hydric propagation diseases.